Cost of Capital, Corporate Reputation and Human Capital Disclosure: A Study of Companies in Indonesia - Setyawan, Setu; Juanda, Ahmad; Inata, Lia Candra (Asian Journal of Applied Business and Management, 2024)
The purpose of this study is to test and analyze the cost of capital and reputation of companies on the Human Resources disclosure. The sample in this study consisted of 318 companies the sample criteria. This research data was analyzed using a regression model of ordinary least square (OLS) estimation technique. Based on testing, researchers found that debt costs and equity costs negatively affect human resource disclosure, while company reputation is positively related to human resource disclosure. In addition, research findings from Indonesia's largest categorized industries show that debt costs and equity costs have a significant negative impact on human capital disclosure. Meanwhile, industries that are not categorized as the largest companies in Indonesia do not show significant results in both debt costs and equity costs. This study got results cost of debt and the cost of equity to human capital disclosure is driven by companies engaged in large-scale industries. This research provides contribution, insight and reference to companies in Indonesia through the HR disclosure index as a benchmark to improve HR disclosure in the future. Also, for policymakers, this research can be a consideration for making policies that HR disclosure practices as mandatory disclosures for companies.